Online anatomy teaching during the COVID-19 pandemic: assessing the perceptions of undergraduate veterinary medical students - Mohamed, Reda; Benjamin, Lisa A; Sahu, Pradeep Kumar (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: To explore veterinary students’ perceptions of online anatomy teaching during the COVID-19 pandemic. Materials and Methods: A cross-sectional study was conducted at the School of Veterinary Medicine, where we collected data from year 1 and 2 undergraduate students. A Google Form link to the questionnaire and an introductory message were sent via email to all 68 students who had participated in an online anatomy class between March 2020 and May 2021. Results: The response rate was 82.2% (56/68). Most students were female (71.43%) and between the ages of 18 and 22 years old (83.93%). Overall, 58.1% of the students found it difficult to learn online anatomy, and most (82%) agreed that it was difficult to learn practical topics online. Nevertheless, 58.9% of the responding students recommended the continued use of online strategies in teaching this subject. Students reported that they could communicate with the lecturer and receive feedback. Perceived benefits of online learning included the convenience of attending class at home and having more available time, as well as the availability of prerecorded videos of course topics. Conclusions: During the pandemic, students got the opportunity to attend online classes from home. Students thought that online practical anatomy was less useful, and this is an area where new ideas can be suggested to help students see how anatomical structures work. J. Adv. Vet. Anim. Res., 9(3): 453–462, September 2022 http://doi.org/10.5455/javar.2022.i614